2022
DOI: 10.3390/bioengineering9080376
|View full text |Cite
|
Sign up to set email alerts
|

Plant Polysaccharides in Engineered Pharmaceutical Gels

Abstract: Hydrogels are a great ally in the pharmaceutical and biomedical areas. They have a three-dimensional polymeric structure that allows the swelling of aqueous fluids, acting as an absorbent, or encapsulating bioactive agents for controlled drug release. Interestingly, plants are a source of biogels, specifically polysaccharides, composed of sugar monomers. The crosslinking of these polymeric chains forms an architecture similar to the extracellular matrix, enhancing the biocompatibility of such materials. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 179 publications
0
10
0
Order By: Relevance
“…29 In contrast to non-biodegradable hydrogels, polysaccharide based hydrogels are preferred for agricultural applications owing to their biodegradable nature. Among polysaccharides, F I G U R E 3 Hydrogels obtained from natural sources and their applications adopted with permission from Bahú et al 33 chitosan elicit and boost defense system of plants. 30 It is also reported that bean treatment along with chitosan inhibited necrosis caused by mosaic virus.…”
Section: Biopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In contrast to non-biodegradable hydrogels, polysaccharide based hydrogels are preferred for agricultural applications owing to their biodegradable nature. Among polysaccharides, F I G U R E 3 Hydrogels obtained from natural sources and their applications adopted with permission from Bahú et al 33 chitosan elicit and boost defense system of plants. 30 It is also reported that bean treatment along with chitosan inhibited necrosis caused by mosaic virus.…”
Section: Biopolymersmentioning
confidence: 99%
“…Hydrogels obtained from natural sources and their applications adopted with permission from Bahú et al 33 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the range of polymers used for the manufacture of hydrogels is limited. These include natural and synthetic polymers, in particular, poly-N-vinylpyrrolidone [ 36 ], polyoxazolines and copolymers of oxazolines [ 37 , 38 , 39 ], polysaccharides [ 40 ], polyurethanes [ 41 ], poly-N-isopropylacrylamide [ 42 ], polyacrylic acid [ 43 ] and others.…”
Section: Introductionmentioning
confidence: 99%
“…But sugar beet pectin has a lower molecular weight and a larger number of acetyl groups, so the gelling ability is lower. Special conditions are required for the gelation of HM pectins [11]:…”
Section: Introductionmentioning
confidence: 99%